Effect of deploying biomedical equipment technician on the functionality of medical equipment in the government hospitals of rural Nepal - Rita Thapa; Alison Yih; Ashish Chauhan; Salomi Poudel; Sagar Singh; Suresh Shrestha; Suresh Tamang; Rishav Shrestha; Ruma Rajbhandari (BMC, 2022)
Abstract Background Medical equipment plays a crucial role in the provision of quality healthcare services, despite this more than 50% of equipment in developing countries are non-functioning due to a lack of appropriate human resources to maintain. To address this problem some government hospitals of Nepal have deployed a mid-level technical cadre called 'Biomedical Equipment Technician' (BMET). This study aims to evaluate the effectiveness of deploying a BMET on the functionality of medical equipment in government hospitals of rural Nepal. Methods We used a mixed-methods approach with a comparative research design. A comprehensive range of 2189 pieces of medical equipment at 22 hospitals with and without BMET were observed to assess their functional status. Medical equipment were stratified into 6 categories based on department and T tests were conducted. We collected qualitative data from 9 BMETs, 22 medical superintendents, and 22 health staff using semi-structured interviews and focus-group discussions. Thematic content analysis was conducted to explore how the BMET's work was perceived. Findings The quantity of non-functional devices in hospitals without BMETs was double that of hospitals with BMETs (14% and 7% respectively, p < 0.005). Results were similar across all departments including General (16% versus 3%, p = 0.056), Lab (15% versus 7%, p < 0.005) and Operation Theater (14% versus 5%, p < 0.005). Hospitals with BMETs had fewer overall non-functional devices requiring simple or advanced repair compared to hospitals without BMETs [3% versus 7% (p < 0.005) simple; 4% versus 6% (p < 0.005) advanced]. In our qualitative analysis, we found that BMETs were highly appreciated by hospital staff. Hospital workers perceived that having a BMET on staff, rather than twice-yearly visits from central-level maintenance technicians, is an effective way to keep medical equipment functional. However, without a favorable working environment, the BMET alone cannot perform optimally. Conclusions Having a BMET at a rural government hospital has a substantial positive effect on the functional status of medical devices at the hospital. BMETs should be deployed at all rural hospitals to increase the functionality of medical devices, thereby improving the working environment and quality of health services provided.